ANALISIS FATWA DSN-MUI TERHADAP HYBRID CONTRACT PADA LEMBAGA KEUANGAN SYARIAH - Sauqi, Muhammad (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
This article is motivated by the implementation of hybrid contracts in Islamic Financial Institutions which is a necessity in the current era for the development of Islamic Financial Institutions, so that its application is supported by the DSN-MUI fatwa that allows hybrid contracts in business transactions. Therefore, this article aims to further analyze the DSN-MUI fatwa regarding the permissibility of hybrid contracts. The methodology used is the recearhe library. First, a hybrid contract is an agreement between two parties to carry out a muamalah that includes two or more contracts. Second, in the fatwa DSN-MUI uses the rules of legal principles the origin of muamalah is that it can include hybrid contracts. Third, according to the fatwa DSN-MUI is allowed shari'i provided that it is not an illegal transaction prohibited in sharia economic law.